Advertisement call and geographical variation in call features of Dendropsophus berthalutzae (Anura: Hylidae) from the Atlantic Rainforest of southeastern Brazil - Forti, Lucas Rodriguez; Martins, Fábio Augusto Miguel; Bertoluci, Jaime (Zootaxa, 2012)
Acoustic signals are the main mode of communication in anurans (Duellman & Trueb 1994). Calls produced by anurans play an essential role during their reproduction (Wells 1977) and advertisement calls emitted by males are, in many cases, species-specific, representing an important character for species recognition (Abrunhosa et al. 2001; Forti et al. 2010). Thus, the formal description of advertisement calls is relevant for anuran taxonomy (Pombal Jr. et al. 1995).